Changes in Macrophage Polarization During Tendon-to-Bone Healing After ACL Reconstruction With Insertion-Preserved Hamstring Tendon: Results in a Rabbit Model. Issue 5 (18th May 2022) - Liu, Shaohua; Lin, Jinrong; Luo, Zhiwen; Sun, Yaying; Wang, Chenghui; Chen, Shiyi; Shang, Xiliang; Chen, Jiwu
Background: Decreasing the proinflammatory M1 macrophages or shifting the polarization status from M1 to M2 phenotype is thought to be beneficial for tendon-to-bone healing. In anterior cruciate ligament reconstruction (ACLR), using an insertion-preserved hamstring tendon (IP-HT) graft compared with a free hamstring tendon (FHT) graft has been shown to reduce graft necrosis and improve healing. However, the role of macrophage polarization at the tendon-to-bone interface is unclear. Hypothesis: ACLR using IP-HT graft would facilitate the phenotype shift from M1 to M2 macrophages at the tendon-to-bone interface. Study Design: Controlled laboratory study. Methods: Unilateral ACLR was performed on 42 healthy New Zealand White rabbits (study group, 21 rabbits with IP-HT graft; control group, 21 rabbits with FHT graft). At days 1, 3, and 7 and weeks 3, 6, 12, and 24 postoperatively, 3 rabbits in each group were sacrificed to investigate and compare the expression of surrogate markers for M1 macrophages (inducible nitric oxide synthase [iNOS] and tumor necrosis factor α [TNF-α]) and M2 macrophages (CD206 and transforming growth factor β [TGF-β]) via immunohistochemical staining and evaluation. Results: In the control group, the percentage of iNOS- and TNF-α–positive cells from postoperative day 7 and week 3 increased then decreased by week 6; positive expression of CD206 and TGF-β was weaker and peaked at 3 weeks postoperatively. In the study group, high CD206- and TGF-β–positive expression was observed from weeks 3 to 12 and peaked at week 6, and positive expression of iNOS- and TNF-α was weaker and peaked on day 7. At both 7 days and 3 weeks, the percentages of iNOS- and TNF-α–positive cells in the control group were both significantly higher than in the study group ( P ≤ .04 for all). At 6 weeks, the percentages of CD206- and TGF-β–positive cells in the study group were both significantly higher than in the control group ( P = .02 and P = .04, respectively). Conclusion: More expression of surrogate markers for M2 macrophages was observed in the tendon-to-bone healing process after ACLR using IP-HT versus FTP graft. Clinical Relevance: Using IP-HT grafts in ACLR may facilitate postoperative healing by shifting the local status of macrophage polarization at the tendon-to-bone interface.